Limonium cophanense (Plumbaginaceae), a new species from Sicily - Brullo, Cristian; Brullo, Salvatore; Cambria, Salvatore; Galdo, Gianpietro Giusso Del; Ilardi, Vincenzo (Phytotaxa, 2016)
Limonium cophanense is described and illustrated as a new species from the rocky coast of northwestern Sicily. It is a very rare and localized chamaephyte occurring near the sea on calcarenitic substrate, where it grows together with other halophytes. Its morphology, ecology, conservation status and relationships with the species belonging to the L. bocconei group are also examined.